KAJIAN PENGARUH PENINGKATAN KONSENTRASI EKSTRAK KHAMIR PADA MEDIA HESTRIN DAN SCHRAMM TERHADAP PEROLEHAN SELULOSA OLEH Acetobacter liquefaciens SRC-4 - Ermina Sari (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2014)
SRC-4 starin is one of bacteria sellulose producing strains. It was obtained from the rottencoconut meat from Semplak, Bogor. The objective of this study is to obtain the optimumcomposition of modified HS medium to produce cellulose, by increasing yeast extractconcentration and also combination of carbon and vitamin sources. The production of celluloseby SRC-4 was done by 18 treatments on static culture. The increasing of yeast extractconcentration, combination of carbon and vitamin sources gave significant effect to theproduction of cellulose. The highest yield of cellulose was produced at the treatment consist of1.0 % yeat extract (as nitrogen source), 1 % glucose + 1 % glycerol (as carbon source) and0.164 ppm vitamin B1 + 0.020 ppm vitamin B2 (as vitamin source).